Administration of N-acetylcysteine Plus Acetylsalicylic Acid Markedly Inhibits Nicotine Reinstatement Following Chronic Oral Nicotine Intake in Female Rats - Quintanilla, María Elena (Front Behav Neurosci, 2021)
BACKGROUND: Nicotine is the major addictive component of cigarette smoke and the prime culprit of the failure to quit smoking. Common elements perpetuating the use of addictive drugs are (i) cues associated with the setting in which drug was used and (ii) relapse/reinstatement mediated by an increased glutamatergic tone (iii) associated with drug-induced neuroinflammation and oxidative stress. AIMS: The present study assessed the effect of the coadministration of the antioxidant N-acetylcysteine (NAC) plus the anti-inflammatory acetylsalicylic acid (ASA) on oral nicotine reinstatement intake following a post-deprivation re-access in female rats that had chronically and voluntarily consumed a nicotine solution orally. The nicotine-induced oxidative stress and neuroinflammation in the hippocampus and its effects on the glutamate transporters GLT-1 and XCT mRNA levels in prefrontal cortex were also analyzed. RESULTS: The oral coadministration of NAC (40 mg/kg/day) and ASA (15 mg/kg/day) inhibited by 85% of the oral nicotine reinstatement intake compared to control (vehicle), showing an additive effect of both drugs. Acetylsalicylic acid and N-acetylcysteine normalized hippocampal oxidative stress and blunted the hippocampal neuroinflammation observed upon oral nicotine reinstatement. Nicotine downregulated GLT-1 and xCT gene expression in the prefrontal cortex, an effect reversed by N-acetylcysteine, while acetylsalicylic acid reversed the nicotine-induced downregulation of GLT-1 gene expression. The inhibitory effect of N-acetylcysteine on chronic nicotine intake was blocked by the administration of sulfasalazine, an inhibitor of the xCT transporter. CONCLUSION: Nicotine reinstatement, following post-deprivation of chronic oral nicotine intake, downregulates the mRNA levels of GLT-1 and xCT transporters, an effect reversed by the coadministration of N-acetylcysteine and acetylsalicylic acid, leading to a marked inhibition of nicotine intake. The combination of these drugs may constitute a valuable adjunct in the treatment of nicotine-dependent behaviors.